The novel synthetic serine protease inhibitor CU-2010 dose-dependently reduces postoperative blood loss and improves postischemic recovery after cardiac surgery in a canine model - Szabó, Gábor; Veres, Gábor; Radovits, Tamás; Haider, Humaira; Krieger, Nelli; Bährle-Szabó, Susanne; Niklisch, Silke; Miesel-Gröschel, Christiane; Locht, Andreas van de; Karck, Matthias (The journal of thoracic and cardiovascular surgery, 2010)
Background - Serine protease inhibitors such as aprotinin reduce perioperative blood loss and may improve postpump cardiac performance owing to their anti-inflammatory properties. After the “aprotinin era,” we investigated the efficacy of the novel synthetic serine protease inhibitors CU-2010 with improved coagulatory and anti-inflammatory profile on blood loss and reperfusion injury in a canine model. - Methods - Thirty-six dogs were divided into 6 groups: control, aprotinin (n = 8; Hammersmith scheme), and CU-2010 (0.5, 0.83, 1.25, and 1.66 mg/kg). All animals underwent 90 minutes of cardiopulmonary bypass with 60 minutes of hypothermic cardioplegic arrest. End points were blood loss during the first 2 hours after application of protamine, as well as recovery of myocardial contractility (slope of the end-systolic pressure-volume relationship, coronary blood flow, and vascular reactivity. - Results - CU-2010 dose-dependently reduced blood loss to a degree comparable with that of aprotinin at lower doses and even further improved at higher doses (control/aprotinin/CU-2010 in increasing doses: 142 ± 13, 66 ± 17, 95 ± 16, 57 ± 17, 46 ± 3, and 13 ± 4 mL; P < .05). Whereas aprotinin did not influence myocardial function, CU-2010 improved the recovery of end-systolic pressure-volume relationship (control 60 ± 6 mg kg vs aprotinin 73 ± 7 mg/kg vs CU-2010 1.66 mg/kg; 102% ± 8%; P < .05). Coronary blood flow (52 ± 4 vs 88 ± 7 vs 96 ± 7; P < .05) and response to acetylcholine (44% ± 6% vs 77% ± 7% vs 81% ± 6%; P < .05) were improved by both aprotinin and CU-2010. - Conclusions - The novel serine protease inhibitor CU-2010 significantly reduced blood loss after cardiac surgery comparable with aprotinin. Furthermore, an additionally improved anti-inflammatory profile led to a significantly improved postischemic recovery of myocardial and endothelial function.
Gesehen am 08.09.2023
Read at the Eighty-ninth Annual Meeting of The American Association for Thoracic Surgery, Boston, Massachusetts, May 9–13, 2009